Thermodynamic and structural analysis of HIV protease resistance to darunavir - analysis of heavily mutated patient-derived HIV-1 proteases - Kožíšek, Milan; Lepšík, Martin; Grantz Šašková, Klára; Brynda, Jiří; Konvalinka, Jan; Rezáčová, Pavlína (The FEBS journal, 2014)
UNLABELLED: We report enzymologic, thermodynamic and structural analyses of a series of six clinically derived mutant HIV proteases (PR) resistant to darunavir. As many as 20 mutations in the resistant PRs decreased the binding affinity of darunavir by up to 13 000-fold, mostly because of a less favorable enthalpy of binding that was only partially compensated by the entropic contribution. X-ray structure analysis suggested that the drop in enthalpy of darunavir binding to resistant PR species was mostly the result of a decrease in the number of hydrogen bonds and a loosening of the fit between the inhibitor and the mutated enzymes. The favorable entropic contribution to darunavir binding to mutated PR variants correlated with a larger burial of the nonpolar solvent-accessible surface area upon inhibitor binding. We show that even very dramatic changes in the PR sequence leading to the loss of hydrogen bonds with the inhibitor could be partially compensated by the entropy contribution as a result of the burial of the larger nonpolar surface area of the mutated HIV PRs. DATABASE: Atomic coordinates and structure factors for the crystal structures PRwt-DRV and PRDRV2-DRV complex have been deposited in the Protein Data Bank under accession codes 4LL3 and 3TTP, respectively. STRUCTURED DIGITAL ABSTRACT: • PR and PR bind by x-ray crystallography (View interaction).
Keywords: X‐ray crystallography; simulace molekulového dockingu; HIV-proteasa; HIV Protease Inhibitors; enthropic contribution; Molecular Sequence Data; Protein Binding; darunavir; molekulární sekvence - údaje; termodynamika; mutace; Molecular Docking Simulation; sulfonamidy; Darunavir; HIV Protease; isothermal titration calorimetry; virová léková rezistence; Amino Acid Sequence; Thermodynamics; vazba proteinů; Drug Resistance, Viral; inhibitory HIV-proteasy; Mutation; HIV protease inhibitors; resistance mutation; Sulfonamides; sekvence aminokyselin